1995
DOI: 10.1111/j.1399-6576.1995.tb04178.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anaesthetic drugs on the lower oesophageal sphincter in propofol/nitrous oxide anaesthetized dogs: Pressure profilometry in an animal model

Abstract: The lower oesophageal sphincter (LES) is the main barrier against gastro-oesophageal reflux. Various anaesthetic drugs have been reported to affect the LES pressure. In this study, the effects of cisapride, atropine, suxamethonium, vecuronium and pancuronium on the LES pressure of six mongrel dogs anaesthetized with propofol and nitrous oxide were investigated. By means of eight-channel pressure profilometry the LES pressure was measured in consecutive sessions before and after administration of each drug. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Gastroesophageal reflux (GOR) is the outflow of gastric content into the oesophagus and is a common complication of general anaesthesia 1–3 . Previously reported rates vary between 16%−60% 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastroesophageal reflux (GOR) is the outflow of gastric content into the oesophagus and is a common complication of general anaesthesia 1–3 . Previously reported rates vary between 16%−60% 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Gastroesophageal reflux (GOR) is the outflow of gastric content into the oesophagus and is a common complication of general anaesthesia. [1][2][3] Previously reported rates vary between 16%−60%. 2,3 Reported consequences range from postoperative discomfort to oesophagitis or oesophageal stricture.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced pressure and consequent reduction in the gastro-esophageal pressure gradient (GEPG) may promote gastro-esophageal reflux, which increases the chances of aspiration, and thus contribute to aspiration pneumonia, pneumonitis, and associated morbidity. Many sedatives and anesthetics reduce lower esophageal sphincter pressure (LESP), but LESP per se is difficult to measure [24]. The relationship between sedation level and lower esophageal sphincter functionality is of considerable clinical interest.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a good correlation between anesthetic dose and reduced LESP [24], suggesting that there may also be an association between sedation level and LESP. We thus evaluated the association between lower esophageal sphincter pressure and 2 measures of sedation: BIS and the responsiveness component of the Observer’s Assessment of Alertness score.…”
Section: Introductionmentioning
confidence: 99%